Atypical postural control can be detected via computer vision analysis in toddlers with autism spectrum disorder. Issue 1 (December 2018) - Dawson, Geraldine; Campbell, Kathleen; Hashemi, Jordan; Lippmann, Steven; Smith, Valerie; Carpenter, Kimberly; Egger, Helen; Espinosa, Steven; Vermeer, Saritha; Baker, Jeffrey; Sapiro, Guillermo
Abstract Evidence suggests that differences in motor function are an early feature of autism spectrum disorder (ASD). One aspect of motor ability that develops during childhood is postural control, reflected in the ability to maintain a steady head and body position without excessive sway. Observational studies have documented differences in postural control in older children with ASD. The present study used computer vision analysis to assess midline head postural control, as reflected in the rate of spontaneous head movements during states of active attention, in 104 toddlers between 16–31 months of age (Mean = 22 months), 22 of whom were diagnosed with ASD. Time-series data revealed robust group differences in the rate of head movements while the toddlers watched movies depicting social and nonsocial stimuli. Toddlers with ASD exhibited a significantly higher rate of head movement as compared to non-ASD toddlers, suggesting difficulties in maintaining midline position of the head while engaging attentional systems. The use of digital phenotyping approaches, such as computer vision analysis, to quantify variation in early motor behaviors will allow for more precise, objective, and quantitative characterization of early motor signatures and potentially provide new automated methods for early autism risk identification.